Sociodemographic, health behavioral, and disease history risk factors for dementia in older adults: a population-based cross-sectional study in Guangzhou, China - Huang, Xinyue; Li, Cuibing; Tao, Guixian; Zhong, Yi; Li, Jiahui; Chen, Tinglong; Shen, Jichuan (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to estimate the prevalence of dementia and its associated risk factors among older adults aged 65 years and above in Guangzhou, China.MethodsWe conducted a community-based cross-sectional study involving 2,463 residents aged 65 years or older in Guangzhou, using a multi-stage whole-population random sampling method. Cognitive function was assessed using the Mini-Mental State Examination (MMSE), with cutoff points adjusted by education level. Trained investigators collected information on demographic characteristics, health behavioral factors, and medical history through face-to-face interviews. Univariate analyses and multivariate logistic regression were performed to identify factors associated with dementia.ResultsThe prevalence of dementia was 14.94% among participants aged 65 and above, increasing from 13.30 to 34.58% across different age groups. Multivariate analysis showed that frequent falls (≥3 falls within the past year vs. no falls: OR = 2.72, 95% CI: 1.27–5.81, p < 0.05), older age (≥85 years vs. 65–74 years: OR = 2.62, 95% CI: 1.66–4.13, p < 0.001), depression (OR = 2.61, 95% CI: 1.36–5.00, p < 0.05) had the most significant associations with dementia risk. Lower educational attainment, prolonged sleep duration (≥8 h), lack of cognitive activity and physical activity, depression, as well as a history of stroke, also showed statistical differences.ConclusionDementia is highly prevalent among older adults in Guangzhou, posing a substantial public health challenge. Our findings emphasize the need for early identification and targeted interventions, including the promotion of physical and cognitive activities, fall prevention strategies, and better management of chronic conditions such as stroke, depression, and hearing loss, to reduce dementia risk and burden in aging communities.